Electrodeposition of Zn Zn-doped Cu Cu2O in Acidic and Alkaline Solution and Its Catalytic Activity for Ethanol Electrooxidation - Setia Budi; Devi Indrawati Syafei (BRIN Publishing (Penerbit BRIN), 2023)
In this study, Zn-doped Cu2O films were synthesized by electrodeposition technique in acidic (pH 4) and alkaline (pH 10) solution. Catalytic activity of the film was evaluated toward ethanol electrooxidation which was carried out using cyclic voltammetry technique. X-ray diffraction (XRD) analysis showed the formation of cubic structure of Cu2O from both conditions. Morphological characterization conducted under a field-emission scanning electron microscope exhibited that Cu2O particles electrodeposited in the acidic condition were smaller compared to those obtained in the alkaline condition. The photoelectrochemical responses, which were recorded using a linear sweep voltammetry technique, showed that the highest photocurrent density was 31.5 mA.cm-2 that obtained at 0.76 V vs. Ag/AgCl using Zn-doped Cu2O film prepared in the acidic condition. The film also possesses a low resistance charge transfer as measured by the electrochemical impedance spectroscopy (EIS) technique. These electrochemical characteristics resulted in a high catalytic performance of the Zn-doped Cu2O film on the ethanol electrooxidation as shown by the high anodic current of 22 mA.cm-2 at 0.968 V. These results indicated that the Zn-doped Cu2O film electrodeposited in the acidic condition has a good catalytic activity towards ethanol electrooxidation process.